Effect of Extraction Conditions on the Antioxidant Activity of Olive Wood Extracts - Mercedes Pérez-Bonilla; Sofía Salido; Adolfo Sánchez; Teris A. van Beek; Joaquín Altarejos (International Journal of Food Science)
An investigation to optimize the extraction yield and the radical scavenging activity from the agricultural by-product olive tree wood (Olea europaea L., cultivar Picual) using six different extraction protocols was carried out. Four olive wood samples from different geographical origin, and harvesting time have been used for comparison purposes. Among the fifty olive wood extracts obtained in this study, the most active ones were those prepared with ethyl acetate, either through direct extraction or by successive liquid-liquid partitioning procedures, the main components being the secoiridoids oleuropein and ligustroside. An acid hydrolysis pretreatment of olive wood samples before extractions did not improve the results. In the course of this study, two compounds were isolated from the ethanolic extracts of olive wood collected during the olives’ harvesting season and identified as (7′′R)-7′′-ethoxyoleuropein (1) and (7′′S)-7′′-ethoxyoleuropein (2).